PAK1 Promotes the Proliferation and Inhibits Apoptosis of Human Spermatogonial Stem Cells via PDK1/KDR/ZNF367 and ERK1/2 and AKT Pathways - Hongyong Fu; Wenhui Zhang; Qingqing Yuan; Minghui Niu; Fan Zhou; Qianqian Qiu; Guoping Mao; Hong Wang; Liping Wen; Min Sun; Zheng Li; Zuping He (Elsevier, 2018)
Spermatogonial stem cells (SSCs) have significant applications in reproductive and regenerative medicine. However, nothing is known about genes in mediating human SSCs. Here we have explored for the first time the function and mechanism of P21-activated kinase 1 (PAK1) in regulating the proliferation and apoptosis of the human SSC line. PAK1 level was upregulated by epidermal growth factor (EGF), but not glial cell line-derived neurotrophic factor (GDNF) or fibroblast growth factor 2 (FGF2). PAK1 promoted proliferation and DNA synthesis of the human SSC line, whereas PAK1 suppressed its apoptosis in vitro and in vivo. RNA sequencing identified that PDK1, ZNF367, and KDR levels were downregulated by PAK1 knockdown. Immunoprecipitation and Western blots demonstrated that PAK1 interacted with PDK1. PDK1 and KDR levels were decreased by ZNF367-small interfering RNAs (siRNAs). The proliferation of the human SSC line was reduced by PDK1-, KDR-, and ZNF367-siRNAs, whereas its apoptosis was enhanced by these siRNAs. The levels of phos-ERK1/2, phos-AKT, and cyclin A were decreased by PAK1-siRNAs. Tissue arrays showed that PAK1 level was low in non-obstructive azoospermia patients. Collectively, PAK1 was identified as the first molecule that controls proliferation and apoptosis of the human SSC line through PDK1/KDR/ZNF367 and the ERK1/2 and AKT pathways. This study provides data on novel gene regulation and networks underlying the fate of human SSCs, and it offers new molecular targets for human SSCs in translational medicine. Keywords: PAK1, human spermatogonial stem cells, proliferation, apoptosis, PDK1/KDR/ZNF367, ERK1/2 and AKT pathways